Al-Tajârib wa al-Taḥadiyyât ‘inda Muta’allimi al-Lughah al-‘Arabiyyah fî âdâi Ikhtibar al-Lughah al-Mi’yârîy (TOAFL) - Rahman, Aulia; Supriani, Ria Rafita (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Purpose- This study aims to describe the experience of STAIN Mandailing Natal Arabic students in taking the TOAFL test, both when taking the TOAFL exam and when doing TOAFL questions. This study also describes the challenges faced by students in taking the TOAFL test.  Design/Methodology/Approach- The study used a qualitative approach based on analytical descriptive methods and used two data collection methods, namely questionnaires and interviews.  Findings- In this study, it can be seen that (1) the average Arabic student is very happy when taking the toafl exam because it can measure their Arabic language skills and not all students are selected in participating in the activity, (2) in doing toafl questions there are difficulties, namely the audio istima is very fast so they cannot hear well and long qiraah questions make students become bored and panic. (3) The challenges faced by students are regarding timing, lack of practice, inadequate facilities and infrastructure and the atmosphere of the exam.  Research Limitation/Implications- With the research, it is expected that all TOAFL organizers will see and pay attention to the factors that are difficulties and challenges in the TOAFL test, especially non-linear factors so that the implementation of the exam can be maximized